1998
DOI: 10.1016/s0928-8244(98)00048-0
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus suis and group B Streptococcus differ in their interactions with murine macrophages

Abstract: Streptococcus suis type 2 and group B Streptococcus type III (GBS) are important encapsulated bacterial species causing meningitis. In the present study we compared quantitatively the uptake and intracellular survival of S. suis type 2 and GBS type III with murine macrophages in non-opsonic conditions. The role of the capsule of both pathogens was also studied using previously obtained unencapsulated isogenic mutants. Encapsulated S. suis wild-type strain was practically not phagocytosed, while the unencapsula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
51
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 17 publications
8
51
1
Order By: Relevance
“…Once in the bloodstream, S. suis resists phagocytosis and killing by neutrophils and monocytes (Chabot-Roy et al, 2006;Charland et al, 1998;Segura et al, 1998;Smith et al, 1999). In the event that S. suis fails to cause acute fatal septicaemia, bacteria are able to reach the CNS via different mechanisms that are only partially elucidated, such as adhesion to, with or without toxicity, and invasion of brain microvascular endothelial cells (BMEC) (Benga et al, 2005;Charland et al, 2000;Vanier et al, 2004) and/or choroid plexus epithelial cells (Tenenbaum et al, 2005(Tenenbaum et al, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Once in the bloodstream, S. suis resists phagocytosis and killing by neutrophils and monocytes (Chabot-Roy et al, 2006;Charland et al, 1998;Segura et al, 1998;Smith et al, 1999). In the event that S. suis fails to cause acute fatal septicaemia, bacteria are able to reach the CNS via different mechanisms that are only partially elucidated, such as adhesion to, with or without toxicity, and invasion of brain microvascular endothelial cells (BMEC) (Benga et al, 2005;Charland et al, 2000;Vanier et al, 2004) and/or choroid plexus epithelial cells (Tenenbaum et al, 2005(Tenenbaum et al, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Our work shows that the ⌬covR mutant survived more than the wild type in human PMNs and MONOs. It is reasonable to explain this phenomenon by the thicker capsule of the ⌬covR strain, since it has been reported that the capsular polysaccharide (CPS) of S. suis protects against phagocytosis and against the bactericidal activity of leukocytes (6,9,48,59,62,63,79). The work of Segura et al demonstrated that S. suis serotype 2 is able to interact with MONOs of human origin, inducing the release of large amounts of the proinflammatory cytokines (61).…”
Section: Discussionmentioning
confidence: 99%
“…Like S. suis, GBS possesses a sialic acid-containing capsule and produces a hemolysin, and different virulence potentials are observed among strains (3,25,54). However, although the two species present similar characteristics, the pathogeneses of the infections caused by the two bacteria may be different (38). It is known that GBS can invade BMEC and that GBS hemolysin can injure lung and brain endothelial cells (18,30).…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently demonstrated that the polysaccharide capsule, which is rich in sialic acid (8), confers antiphagocytic properties on S. suis. Acapsular mutants were readily phagocytosed by murine and porcine macrophages, unlike the wildtype strain (7,38,39). Furthermore, S. suis capsule is a virulence factor in the murine and porcine infection models since acapsular mutants were nonpathogenic and more rapidly cleared from the bloodstream than the wild-type strain (7).…”
mentioning
confidence: 96%